IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN BAHASA INDONESIA PADA SISWA KELAS VIII SMP NEGERI 1 KECAMATAN AKABILURU KABUPATEN LIMA PULUH KOTA - Zahratul Ummami; Zulfikarni; Nursaid; Delsy Arma Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this research is to explain how eighth-grade students at SMP Negeri 1 Akabiluru, Limapuluh Kota Regency, are studying Indonesian while receiving character education. The planning, execution, assessment, and enabling and impeding elements of character education integration are the four main areas of attention for the study. The qualitative descriptive approach was used in this study. Documentation, interviews, and observations were used to gather data. Data reduction, data presentation, and conclusion drawing were all done in accordance with Miles and Huberman's interactive model. The results show that throughout the planning phase, character values ​​were methodically included into the lesson plans. During the implementation phase, classroom activities were used to apply the six Pancasila Student Profile aspects. Evaluation was carried out to continuously improve character development in addition to evaluating academic performance. While time constraints, student motivation, and environmental issues are hindering factors, school facilities and principal assistance are supporting elements. The study comes to the conclusion that while character education has been successfully included into Indonesian language instruction, ongoing enhancement is required to maximize its benefits.